Comparison between color stability of zirconia and lithium disilicate - Alfaer, Ali S.; Hamdi, Bassam A.; Melibary, Raghad T.; Alfwais, Ryan H.; Asirri, Naif M.; Darweesh, Rawa A.; Albazi, Lateefa M.; Alalawi, Faten H.; Asiri, Abdulaziz M.; Alshehri, Hassan A.; Albuqayli, Asrar S. (International Journal Of Community Medicine And Public Health, 2022)
The most widely used glass-ceramic is lithium disilicate (LD) because of its remarkable optical qualities, high strength, and simplicity of manufacture. Greater marginal strength, reduced porosity, and net-shaped manufacturing by pressing are further benefits of LD. The development of yttrium stabilized trigonal zirconia polycrystalline (Y-TZP) ceramics is the result of the pursuit for a material with both mechanical capabilities, like the resistance provided by metallic restoration, and the distinctive optical characteristics of glass-ceramic. The main drawback is the fragile veneering ceramics, which are prone to chipping, debonding, and breakage. There is evidence that extrinsic variables such beverages, mouthwashes, acid solutions, dental brushing, and increased temperatures might cause ceramic surfaces to deteriorate. The composition and surface shape of ceramic materials have an impact on the extrinsic pigment absorption or adsorption from the oral cavity. The main causes for the clinical replacement of anterior restorations, according to prior research, are poor color matching and color instabilities. Monolithic zirconia is more prone to staining from chlorhexidine, green tea, and coffee. In monolithic zirconia, the aging-related color changes are more pronounced. The color of the background substructure influences how zirconia restorations look overall. In terms of color stability and translucency, LD ceramic has also been proven to be more aesthetically pleasing. In comparison to monolithic zirconia, bilayer zirconia with feldspar veneering ceramic displayed reduced discoloration overall. It has been noted that monolithic zirconia is more susceptible to low-temperature degradation than the core Y-TZP. The use of current literature to infer outcomes has several limitations because in most vitro investigations, thermocycling has been carried out in water rather than oral cavity saliva and the influence of sunlight exposure, salivary proteins, food coloring, tobacco, different enzymes, and surface-related factors on the color stability is yet to be examined.